Fluid migration before and after a large megathrust earthquake - Alexander Wickham-Piotrowski; Anne Meltzer; Gabriela Ponce; Susan Beck; Sandro Vaca; Monica Segovia; Steven Roecker; Mario Ruiz; Stephen Hernandez (Earth and Planetary Science Letters, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

6-PPD induces mitochondrial dysfunction and reduces healthspan and lifespan through SKN-1 in Caenorhabditis elegans - Moonjung Hyun; Laxmi Rathor; Hye-Jin Kim; Ho-Jeong Lee; Taylor McElroy; Moongi Ji; Min-Seok Choi; Steven Beck; Julia Bailey; Hun Hwan Kim; Yi Sheng; Jeong-Doo Heo; et al. (Journal of Hazardous Materials, 2025)

Multi-millennia slip rate relationships between closely spaced across-strike faults: Temporal earthquake clustering of the Skinos and Pisia Faults, Greece, from in situ 36Cl cosmogenic exposure dating - Sam Mitchell; Claudia Sgambato; Jenni Robertson; Gerald P. Roberts; Joanna P. Faure Walker; Zoë Mildon; Athanassios Ganas; Ioannis Papanikolaou; Francesco Iezzi; Joakim Beck; Steven A. Binnie; Tibor Dunai; et al. (Journal of Structural Geology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A community-centric intelligent cyberinfrastructure for addressing nitrogen pollution using web systems and conversational AI - Samrat Shrestha; Jerry Mount; Gabriel Vald; Yusuf Sermet; Dinesh Jackson Samuel; Chelsea Bryant; Ana C. Peralta; Marcus W. Beck; Steven D. Meyers; Frank E. Muller-Karger; David Cwiertny; Ibrahim Demir (Environmental Science & Policy, 2025)

Effect of PLGA raw materials on in vitro and in vivo performance of drug-loaded microspheres - Desheng Liang; Jennifer Walker; Peter S. Schwendeman; Aishwarya Chandrashekar; Rose Ackermann; Karl F. Olsen; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2025)

Developing a Genetic Algorithm for Selecting Infrastructure Modifications that Optimize Hydrodynamic Flushing in Old Tampa Bay - Steven D. Meyers; Marcus W. Beck; Edward T. Sherwood; Mark E. Luther (Estuaries and Coasts, 2024)
Impermeable infrastructure such as traffic causeways can reduce the natural hydrodynamic flushing of an estuary, resulting in reduced water quality and increased incidence of harmful algal blooms (HABs). A series of cuts through the three causeways spanning Old Tampa Bay, FL, (OTB) are being considered to help restore the natural circulation of the region, but the number of possible location combinations is computationally challenging to fully assess. A prototype genetic algorithm (GA) was developed to identify the optimal configuration of these cuts through one of the bridge sections that maximizes flushing as represented in a numerical ocean circulation model of OTB. Flushing was measured by integrating the trajectories of over 21,000 passive Lagrangian “particles” using the model velocity fields. The rate of loss of particles initialized near Feather Sound (a region subject to frequent HABs) was used to quantify the “fitness” over which the configurations were optimized. The highest-scoring solution produced a 42% increase in net flushing compared to a no-change baseline. Six independently initialized applications of the GA were conducted. All converged to the same solution within no more than 7 generations. The small population size of the prototype allowed testing of the complete solution space, and verification the found solution was optimal. Elitism (preservation of the highest-ranking solution) was required for convergence. The GA also identified configurations that had similar, but slightly slower, flushing rates. These results will help area managers prioritize or rank combinations of causeway modifications to improve overall water quality conditions in Tampa Bay.

Post‐glacial recolonization and multiple scales of secondary contact contribute to contemporary Atlantic salmon ( Salmo salar ) genomic variation in North America - Cameron M. Nugent; Tony Kess; Barbara L. Langille; Samantha V. Beck; Steven Duffy; Amber Messmer; Nicole Smith; Sarah J. Lehnert; Brendan F. Wringe; Matthew Kent; Paul Bentzen; Ian R. Bradbury (Journal of Biogeography, 2024)
Aim In northern environments, periods of isolation during Pleistocene glaciations and subsequent recolonization and secondary contact have had a significant influence on contemporary diversity of many species. The recent advent of high‐resolution genomic analyses allows unprecedented power to resolve genomic signatures of such events in northern species. Here, we provide the highest resolution genomic characterization of Atlantic salmon in North America to date to infer glacial refugia and the geographic scales of post‐glacial secondary contact. Location North America. Taxon Atlantic salmon, Salmo salar . Methods Samples were collected for 5455 individuals from 148 populations, encompassing the majority of the Atlantic salmon's native range in North America, from Labrador to Maine. Individuals were genotyped using a 220K single nucleotide polymorphism array aligned to the Atlantic salmon ( Salmo salar ) genome. Spatial genetic structure (principal component analysis, k ‐means clustering, admixture) was evaluated in conjunction with genomic comparisons of these identified lineages to infer the refugia during the last glacial maximum and regions of secondary contact following recolonization. Results Spatial genomic analyses identified three phylogeographic groups, consistent with the northward recolonization from two southern glacial refugia in North America (a western Maritime lineage and an eastern Newfoundland and Labrador lineage), with subsequent differentiation of the eastern lineage into two separate groups. Secondary contact among these North American groups was observed within the northern Gulf of St. Lawrence, and evidence of trans‐Atlantic secondary contact was detected within the eastern Newfoundland and Labrador lineage. Comparison of groups from insular Newfoundland with those from mainland Labrador suggests genomic regions displaying high differentiation were characterized by elevated European admixture, suggesting a possible role of European secondary contact in population divergence. Main Conclusions These findings present the first evidence suggesting that genomic diversity in extant North American Atlantic salmon populations has resulted from allopatric isolation in two glacial refugia followed by both regional and trans‐Atlantic recolonization and secondary contact and demonstrate the power of genomic tools to resolve historical drivers of diversity in wild populations.

In vitro degradation and erosion behavior of commercial PLGAs used for controlled drug delivery - Jennifer Walker; Jason Albert; Desheng Liang; Jing Sun; Richard Schutzman; Raj Kumar; Cameron White; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2023)

Correction to: Characterization of commercial PLGAs by NMR spectroscopy - Jing Sun; Jennifer Walker; Moritz Beck‑Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2022)

Characterization of commercial PLGAs by NMR spectroscopy - Jing Sun; Jennifer Walker; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2022)

How Much Marsh Restoration Is Enough to Deliver Wave Attenuation Coastal Protection Benefits? - Katherine A. Castagno; Neil K. Ganju; Michael W. Beck; Alison A. Bowden; Steven B. Scyphers (Frontiers in Marine Science, 2022)
As coastal communities grow more vulnerable to sea-level rise and increased storminess, communities have turned to nature-based solutions to bolster coastal resilience and protection. Marshes have significant wave attenuation properties and can play an important role in coastal protection for many communities. Many restoration projects seek to maximize this ecosystem service but how much marsh restoration is enough to deliver measurable coastal protection benefits is still unknown. This question is critical to guiding assessments of cost effectiveness and for funding, implementation, and optimizing of marsh restoration for risk reduction projects. This study uses SWAN model simulations to determine empirical relationships between wave attenuation and marsh vegetation. The model runs consider several different common marsh morphologies (including systems with channels, ponds, and fringing mudflats), vegetation placement, and simulated storm intensity. Up to a 95% reduction in wave energy is seen at as low as 50% vegetation cover. Although these empirical relationships between vegetative cover and wave attenuation provide essential insight for marsh restoration, it is also important to factor in lifespan estimates of restored marshes when making overall restoration decisions. The results of this study are important for coastal practitioners and managers seeking performance goals and metrics for marsh restoration, enhancement, and creation.

Developing a Water Quality Assessment Framework for Southwest Florida Tidal Creeks - Michael R. Wessel; Jay R. Leverone; Marcus W. Beck; Edward T. Sherwood; Jennifer Hecker; Steven West; Anthony Janicki (Estuaries and Coasts, 2022)
The three contiguous National Estuary Programs of southwest Florida, along with partners from six coastal counties, have developed a tidal creek water quality assessment framework to help prioritize natural resource investigations across a large population of tidal creeks between Tampa Bay and Estero Bay, Florida. The assessment framework is based on outcomes of a multidisciplinary study and includes a nutrient based report card that characterizes nutrient conditions relative to regional numeric nutrient criteria developed for contributing freshwater streams, identification of site-specific water quality indicators of tidal creek condition, and an online open science dashboard to display the assessment framework and provide access to all information relevant to its implementation. Application of the assessment framework has provided an actionable list of southwest Florida tidal creeks prioritized for further research and potential management action along with a host of site-specific indicator results that provide insights into drivers of tidal creek condition. The open science dashboard provides a platform for dissemination of this information in a readily accessible and reproducible format and a means to incorporate new data and indicators as they become available. Local resource managers are in need of tools to help prioritize natural resource investigations and management actions that achieve the greatest resource benefit with limited available resources. This assessment framework informs these efforts and builds capacity for future research to identify and refine management tools for these creeks where management resources, data, and sentinel biological response endpoints are limited.

The early marine distribution of Atlantic salmon in the North‐east Atlantic: A genetically informed stock‐specific synthesis - John Gilbey; Kjell Rong Utne; Vidar Wennevik; Alexander Christian Beck; Kyrre Kausrud; Kjetil Hindar; Carlos Garcia de Leaniz; Corrine Cherbonnel; Jamie Coughlan; Tom F. Cross; Eileen Dillane; Dennis Ensing; et al. (Fish and Fisheries, 2021)
The survival of Atlantic salmon ( Salmo salar) , an increasingly rare anadromous species, has declined dramatically during its marine phase, with disproportionate impacts on the poorly understood early post‐smolt period. Logistical constraints on collecting oceanic data to inform this issue pose a formidable obstacle. To advance understanding of post‐smolt distributional ecology in the North‐east Atlantic, a comprehensive analysis of existing information was undertaken. Data were synthesized from 385 marine cruises, 10,202 individual trawls, and 9,269 captured post‐smolts, spanning three decades and ~4.75 million km 2 of ocean, with 3,423 individuals genetically assigned to regional phylogeographic origin. The findings confirm major migrational post‐smolt aggregations on the continental shelf‐edge off Ireland, Scotland and Norway, and an important marine foraging area in the Norwegian Sea. Genetic analysis shows that aggregational stock composition does not simply reflect distance to natal rivers, with northern phylogeographic stock groups significantly under‐represented in sampled high‐seas aggregations. It identifies a key foraging habitat for southern European post‐smolts located in international waters immediately west of the Vøring Plateau escarpment, potentially exposing them to a high by‐catch mortality from extra‐territorial pelagic fisheries. Evidence of the differential distribution of regional stocks points to fundamental differences in their migration behaviours and may lead to inter‐stock variation in responses to environmental change and marine survival. The study shows that understanding of post‐smolt marine ecology, as regards to stock‐specific variations in habitat utilization, biological performance and exposure to mortality factors, can be significantly advanced by data integration across studies and exploiting genetic approaches.

Zea mays Volatiles that Influence Oviposition and Feeding Behaviors of Spodoptera frugiperda - Jessica P. Yactayo-Chang; Jorrel Mendoza; Steven D. Willms; Caitlin C. Rering; John J. Beck; Anna K. Block (Journal of Chemical Ecology, 2021)

Posttraumatic stress symptom persistence across 24 years: association with brain structures - Carol E. Franz; Sean N. Hatton; Richard L. Hauger; M. Alexandra Kredlow; Anders M. Dale; Lisa Eyler; Linda K. McEvoy; Christine Fennema-Notestine; Donald Hagler; Kristen C. Jacobson; Ruth E. McKenzie; Matthew S. Panizzon; et al. (Brain Imaging and Behavior, 2020)

Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate - Whitney R. Friedman; Benjamin S. Halpern; Elizabeth McLeod; Michael W. Beck; Carlos M. Duarte; Carrie V. Kappel; Arielle Levine; Robert D. Sluka; Steven Adler; Casey C. O’Hara; Eleanor J. Sterling; Sebastian Tapia-Lewin; et al. (Frontiers in Marine Science, 2020)

Aerosol Pirfenidone Pharmacokinetics after Inhaled Delivery in Sheep: a Viable Approach to Treating Idiopathic Pulmonary Fibrosis - Lisa M Kaminskas; Cornelia B Landersdorfer; Robert J Bischof; Nathania Leong; Jibriil Ibrahim; Andrew N Davies; Stephen Pham; Steven Beck; A. Bruce Montgomery; Mark W Surber (Pharmaceutical Research, 2020)

Elevational species richness gradients in a hyperdiverse insect taxon: a global meta‐study on geometrid moths - Jan Beck; Christy M. McCain; Jan C. Axmacher; Louise A. Ashton; Florian Bärtschi; Gunnar Brehm; Sei‐Woong Choi; Oldrich Cizek; Robert K. Colwell; Konrad Fiedler; Cristina L. Francois; Steven Highland; et al. (Global Ecology and Biogeography, 2017)
Aims We aim to document elevational richness patterns of geometrid moths in a globally replicated, multi‐gradient setting, and to test general hypotheses on environmental and spatial effects (i.e. productivity, temperature, precipitation, area, mid‐domain effect and human habitat disturbance) on these richness patterns. Location Twenty‐six elevational gradients world‐wide (latitudes 28° S to 51° N). Methods We compiled field datasets on elevational gradients for geometrid moths, a lepidopteran family, and documented richness patterns across each gradient while accounting for local undersampling of richness. Environmental and spatial predictor variables as well as habitat disturbance were used to test various hypotheses. Our analyses comprised two pathways: univariate correlations within gradients, and multivariate modelling on pooled data after correcting for overall variation in richness among different gradients. Results The majority of gradients showed midpeak patterns of richness, irrespective of climate and geographical location. The exclusion of human‐affected sampling plots did not change these patterns. Support for univariate main drivers of richness was generally low, although there was idiosyncratic support for particular predictors on single gradients. Multivariate models, in agreement with univariate results, provided the strongest support for an effect of area‐integrated productivity, or alternatively for an elevational area effect. Temperature and the mid‐domain effect received support as weaker, modulating covariates, while precipitation‐related variables had no explanatory potential. Main conclusions Despite the predicted decreasing diversity–temperature relationship in ectotherms, geometrid moths are similar to ants and salamanders as well as small mammals and ferns in having predominantly their highest diversity at mid‐elevations. As in those comparative analyses, single or clear sets of drivers are elusive, but both productivity and area appear to be influential. More comparative elevational studies for various insect taxa are necessary for a more comprehensive understanding of elevational diversity and productivity.

IL1B gene promoter haplotype pairs predict clinical levels of interleukin-1β and C-reactive protein - John Rogus; James D. Beck; Steven Offenbacher; Kenneth Huttner; Licia Iacoviello; Maria Carmela Latella; Monica de Gaetano; Hwa-Ying Wang; Kenneth S. Kornman; Gordon W. Duff (Human Genetics, 2008)

The Role of Cohort Studies in Drug Development: Clinical Evidence of Antiviral Activity of Serotonin Reuptake Inhibitors and HMG-CoA Reductase Inhibitors in the Central Nervous System - Scott L. Letendre; Jennifer Marquie-Beck; Ronald J. Ellis; Steven Paul Woods; Brookie Best; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina Marra; Justin C. McArthur; J. Allen McCutchan; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2007)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Coarse Filter Ecosystem Management in a Nonequilibrating Forest - Glen W. Armstrong; Wiktor L. Adamowicz; James A. Beck; Steven G. Cumming; Fiona K.A. Schmiegelow (Forest Science, 2003)
The natural disturbance model of forest management is the basis of many of the sustainable forest management systems being proposed for the boreal forest of Canada. Wildfire is the dominant natural agent of disturbance in the boreal mixed-wood forest. The natural disturbance model assumes that timber harvesting systems emulating the annual area burned by natural fire, its spatial distribution, and the amount of residual material can be developed. It is further assumed that natural processes can be emulated closely enough to maintain forest biota at natural or near-natural population levels. This is a coarse filter approach to ecosystem management. In order to emulate the natural rate of disturbance, one needs to quantify it. The annual area burned in the study area, under natural conditions, is characterized as a random draw from a lognormal distribution. A modeling system comprised of an aspatial Monte Carlo simulation model and a linear programming based forest activity scheduling model was developed. The simulation model is used to develop 200 yr forecasts of probability distributions for habitat area of five vertebrate species under a stochastic wildfire regime. These probability distributions are used to construct habitat area constraints for use in an optimization model to help quantify the trade-offs between timber values and maintenance of the range of natural variability in the forest. The model is used to identify the trade-offs between forest harvesting, wildlife habitat, and the degree of similarity between the managed forest structure and the distribution of structures that could be generated by natural disturbance. FOR. SCI. 49(2):209–223.

GROWTH AND DEVELOPMENT IN FREE‐RANGING HARBOR SEAL ( PHOCA VITULINA ) PUPS FROM SOUTHERN BRITISH COLUMBIA, CANADA - Paul E. Cottrell; Steven Jeffries; Brian Beck; Peter S. Ross (Marine Mammal Science, 2002)
A bstract Harbor seals ( Phoca vitulina ) are small pinnipeds that are widely distributed throughout the temperate coastal regions of the Atlantic and Pacific oceans. We determined birth mass, neonatal growth rates, weaning age, and weaning mass of NE Pacific harbor seals ( P. v. richardsi ) during a capture‐recapture study that spanned the nursing period (Sidney Island, British Columbia, Canada). Of 46 harbor seal pups initially captured, 28 were classified as newborns ( i. e. , P. v. concolor ), British Columbia harbor seals are characterized by half the daily mass gain and a longer nursing period.

Yield and quality evaluations on a pair of processing tomato lines nearly isogenic for the Tm2a gene for resistance to the tobacco mosaic virus - Steven D. Tanksley; Dario Bernachi; Teresa Beck-Bunn; Davy Emmatty; Yuval Eshed; Shuji Inai; Joachin Lopez; Vincent Petiard; Haruki Sayama; John Uhlig; Daniel Zamir (Euphytica, 1998)